University proceedings. Volga region. Technical sciences - I.I. Voyachek; D.V. Kochetkov; A.D. Tarkhanov; Yu.V. Istomina (Известия высших учебных заведений. Поволжский регион:Технические науки)
Background. The generally accepted design methodology for tension joints uses the method of complete interchangeability or the probability-theoretical method. When implementing these methods, the vast majority of connections in a batch have a significantly excess safety factor, which leads to additional costs. The possibility of strengthening joints during assembly, for example, by using anaerobic materials, allows for a different, more rational approach to their design. Materials and methods. The proposed method is based on the assumption that a certain (specified) part of a batch of compounds will be strengthened by using anaerobic materials, since it cannot transfer the operational load with the designated safety margin. A probabilistic approach is used. Normal and uniform distributions of part sizes in a batch are considered. Results. The theoretical substantiation of the new method and confirmation of its effectiveness in computer modeling of the manufacturing process of a batch of tension joints are presented. Conclusions. The technique allows to significantly reduce the level of tension in the connection and assign wider tolerances to the dimensions of the mating parts without losing functional properties.